2018
DOI: 10.1029/2018gh000168
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Disease Burden From Ambient Ozone Exposure in India

Abstract: Long‐term ambient ozone (O3) exposure is a risk factor for human health. We estimate the source‐specific disease burden associated with long‐term O3 exposure in India at high spatial resolution using updated risk functions from the American Cancer Society Cancer Prevention Study II. We estimate 374,000 (95UI: 140,000–554,000) annual premature mortalities using the updated risk function in India in 2015, 200% larger than estimates using the earlier American Cancer Society Cancer Prevention Study II risk functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 121 publications
(302 reference statements)
1
18
2
Order By: Relevance
“…These results are over 3 times higher than our study. Again, inclusion of residential coal combustion in the residential energy use sector as shown in Conibear et al (2018aConibear et al ( , 2018b for India and Zhao et al (2018) for China is the main reason leading to the lower estimates in our study. Moreover, Zhao et al (2018) considers household (indoor) air pollution as part of the associated PM 2.5 exposure estimates, whereas our study only focuses on ambient PM 2.5 and O 3 exposure.…”
Section: 1029/2020gh000362contrasting
confidence: 58%
See 3 more Smart Citations
“…These results are over 3 times higher than our study. Again, inclusion of residential coal combustion in the residential energy use sector as shown in Conibear et al (2018aConibear et al ( , 2018b for India and Zhao et al (2018) for China is the main reason leading to the lower estimates in our study. Moreover, Zhao et al (2018) considers household (indoor) air pollution as part of the associated PM 2.5 exposure estimates, whereas our study only focuses on ambient PM 2.5 and O 3 exposure.…”
Section: 1029/2020gh000362contrasting
confidence: 58%
“…At the national scale, annual total PM 2.5 and O 3 -induced premature deaths in India for the year 2010 from solid biofuel stove sector were 110,100 (95CI: 100,200), which agrees reasonably well with Chowdhury et al (2019), as shown in Figure 8b. However, Conibear et al (2018bConibear et al ( , 2018a reported that PM 2.5 -induced and O 3 -induced annual premature deaths associated with residential energy use for the year 2015 in India were 256,000 (95CI: 162,000-340,000) and 41,000 (95CI: 15,000-61,000), respectively, which were roughly a factor of 2.74 and 2.47 higher than the corresponding averaged annual total PM 2.5 -induced and O 3 -induced premature deaths associated with solid biofuel stove emissions in India from our study (Figure 8b). In China, Zhao et al (2018) estimated that there were about 400,000 (95CI: 250,000-640,000) annual avoided premature deaths for the year 2015 from the solid fuel use attributable to ambient and household PM 2.5 exposure (Figure 8c).…”
Section: 1029/2020gh000362mentioning
confidence: 99%
See 2 more Smart Citations
“…1d). As a result, extreme pollution episodes not only cause PM-related health issues but also increase the risk of chronic obstructive pulmonary disease (COPD) (the most important health outcome of ozone pollution) (Conibear et al, 2018b;US Environmental Protection Agency, 2013).…”
Section: Introductionmentioning
confidence: 99%